STROKE PREVENTION AWARENESS AND PRACTICES AMONG MEDICAL STAFF IN A NIGERIAN TERTIARY HEALTHCARE SETTING - Oluwaseun , Michael Adediran; Okafor , Chidinma Grace (Research Journal of Nursing and Clinical Practice, 2024)
Introduction: Stroke is increasingly a problem of public health significance globally. It is a major cause of disability and mortality. Healthcare professionals must have a good attitude, sufficient knowledge, and practice of stroke prevention to reduce the burden of the disease. Methods: This study utilized a cross-sectional design among 200 Healthcare workers in the Federal Medical Centre, Asaba, Nigeria, selected by systematic sampling technique. A semi-structured questionnaire was used to collect data on the research variables. Data were analyzed using the IBM SPSS version 25 statistical package. Results: A total of 200 Healthcare workers participated in the study. About 77% and 84% of respondents have good aggregate attitudes and knowledge towards stroke prevention respectively. This did not influence their poor practice (54%) of stroke prevention. There was a significant association (p < 0.0001) of good knowledge of stroke by Clinical Healthcare workers [Chi-squares =27.1, 95%CI= (0.029 0.256)] when compared with non-clinical healthcare workers. This is in contrast with their poor practice of stroke prevention (Chi squares=3.570, p = 0.02, 95%CI (0.321-1.023). However, there was no significant association (p=0.423) between the good attitude toward stroke prevention by the Clinical Health care workers [Chi square=0.130, 95%CI= (0.458-1.713)], when compared with Non Clinical Health care workers. Conclusion: It is possible to improve the practice of stroke prevention by encouraging health educational programs on Knowledge and behavior-changing strategies towards stroke prevention.